ANALYSIS OF MULTIPLE INTELLIGENCES EDUCATION POLICIES IN INTEGRATED ISLAMIC SCHOOLS (SDIT) INSAN MANDIRI KALISARI JAKARTA TIMUR - Agung NUGROHO; Rismita RISMITA; Istaryatiningtias ISTARYATININGTIAS (Journal of Education and Leadership in Education, 2020)
This study aims to analyze, to get information on whether the implementation of the multiple intelligences education policy in the Insan Mandiri Kalisari Integrated Islamic Elementary School, East Jakarta, is in accordance with Howard Gardner's theory of multiple intelligences, that each student has the intelligence and uniqueness of one another. This research is categorized as a qualitative research type, using descriptive analytical methods to describe and explain the learning management system, both from primary sources, namely the Insan Mandiri Kalisari Elementary School, East Jakarta documents, and secondary sources, namely research supporting data from books, journals, and articles. The implementation of the theory of multiple intelligences in the scope of education and teaching in schools, includes student input starting from research on intelligence trends or learning styles using multiple intelligences research, the education process and teacher teaching using choice strategies based on the results of research on student learning styles, and educational output through Authentic assessments carried out during the learning process. The results of this study indicate that teachers who know and understand the dominant learning styles of students, and use teaching strategies that are in accordance with the learning styles of students will produce a fun learning process. The implementation of the learning process according to the learning styles of students is applied through a learning management system.